Bulletin Builder: Insights from Bulletin Builder usability testing - Lopez, Sebastian; Hernandez, Victor Manuel; Londoño, Juan Manuel; Sotelo, Steven; Zapata Caldas, Emmanuel (2025)
The Bulletin Builder is an open, web-based platform designed to automate the creation of agroclimatic bulletins. Usability testing of this tool was conducted in two countries, Vietnam and Guatemala, to assess the intuitiveness, understandability, and alignment with users’ mental models of the platform’s interface, workflow, and visual design. In Vietnam, seven participants from regional and national agricultural institutions took part in usability testing with medium-fidelity prototypes. We applied a qualitative, task-based methodology combining think-aloud protocols and moderated testing to evaluate the full end-to-end bulletin creation process. The findings suggest that, while not immediately intuitive, users find the platform useful and relevant for reducing the technical workload. Key improvement opportunities include greater automation of forecast inputs, clearer workflow sequencing, structured data entry via drop-down menus, stronger integration between the crops and pests modules, and greater flexibility during export and final review. In Guatemala, the study evaluated an operational pilot with four users from one private entity and one public entity. The test combined think-aloud methods and A/B testing to compare light and dark interface versions. The results showed high task completion rates and positive perceptions of clarity and efficiency, as well as mixed but complementary visual preferences. Overall, the findings demonstrate Bulletin Builder’s strong potential to facilitate the time-consuming task of regularly developing bulletins (in some cases, every 10 days) while identifying concrete design refinements to improve usability, learnability, and scalability across contexts.